Rheological behaviour and microstructural properties of dark chocolate produced by combination of a ball mill and a liquefier device as small scale chocolate production system. (February 2019) - Saputro, Arifin Dwi; Van de Walle, Davy; Caiquo, Bobby Antan; Hinneh, Michael; Kluczykoff, Martina; Dewettinck, Koen
Abstract: An alternative chocolate processing method, which can be applied by small-scale chocolate industries in cocoa producing countries, is highly needed. This work investigated the impact of processing variables and lecithin concentration on the rheological behaviour and microstructural characteristics of dark chocolate produced by means of a ball mill coupled with a liquefier device. Three experimental variables, namely ball size, milling time and lecithin concentration were studied. To investigate the degree of cocoa butter released from the cocoa particles during the chocolate production, two different cocoa sources, which had different level of cocoa butter, namely cocoa mass and cocoa powder, were used as ingredient. As references, chocolates were also conventionally produced using a combination of a planetary mixer, roll-refiner and conche. The results showed that regardless of the lecithin concentration, ball size, milling time and their interaction were the most decisive experimental variables in the milling process. Furthermore, lecithin concentration, ball size and milling time as well as their interactions highly influenced the rheological behaviour of the chocolates. Moisture and free fat content of the chocolates were comparable regardless of the processing method and the type of cocoa used. Regardless of the cocoa source, Casson yield values of the chocolates produced by alternative processing were higher than those of the chocolates produced by conventional processing, while Casson viscosities were relatively similar. Highlights: Chocolate was produced using a combination of ball mill and liquefier device. Irrespective of the cocoa source and shearing system, all chocolates had comparable free fat content. Viscosity parameters were influenced by particle size and surface morphology of the solids. Microstructure images showed the solid particle arrangement in the chocolate suspension. Liquefaction process was important to create homogeneous chocolate mass.